Os desafios do professor de biologia na promoção de saúde na escola pública: metodologias ativas de aprendizagem como caminho para a superação - Lousan, Nathalie Emanuelle Pigoretti (2015)
The health transverse theme, wich is present at the curriculum proposal (PC) from the departament of education from the state of Sao Paulo- SEE-SP, it its subscribed in the subject of Biology that have a goal to apply its contents and concepts to practice a reflexive and conscious citzenship on the questions of evolution of natural life and human life, within all diversity of organization and interaction. One of the biology teacher's atributions is to articulate the proposal themes from the curriculum into works to promote health and to prevent deseases, taking in consideration, the specific needs of each school community, because in this way, they can contribute for effective learning of the student to increase his quality of life. However, many of these professionals find difficult to relate the PC activities from SEE-SP contain in the teacher's and student notebooks of the biology subject into actual preventive actions. Facing this reality, it was pretend with this study to identify the diadatic pedagogy resources that are used by the teachers to work the theme about health, the easy and hard ways of the work, as a feedback of the students and the feeling of responsability about the student health,that is manifested on the teacher. Besides that, we were looking for the evidence of these actors perception about the active metadology of learning and its application in health education. For the data collecting were made 24 interviews semi stuctured by teachers that belong from Unit School (U.E), the board of eduaction from Votorantim (D.E Vot). On the data organization it was used the colective subject speech (DSC) and the words clouds to visualize the procedure of the words that contained on the interviewer s speech. For the analisys it was used the content analisy (AC), category theme analisy (AT). It was shown that even melding pedagogic didatics resources that are part of a traditional and participative class, having the feeling of responsability of the students health, the teachers have a difficulty to mesuare the feedback of the students after the health themes study, those who notices something is always in a subjective way.The major suporters for the work with themes that are related to your day by day, the improvement of your previous knowlogy and experiences that they arrive in school and the use of resources and metadology of different studies. They do not know the active metadology of learning, but they have the desire to know beliving that it can contribute of positive learning of the students and with the health education in a school enviroment. To conclude, it its propose for the biology teachers the capacitation and implementation of learning based in teams- at first to work with health relate theme- that one of the modalities is the active metadology of learning can contribute with the real knowledge of the students but also for the fix education of teachers, besides it can be apply to a large number of students